'There's nothing really they can do with this information': unpacking how users manage privacy boundaries for personal fitness information. Issue 7 (6th June 2020) - Zimmer, Michael; Kumar, Priya; Vitak, Jessica; Liao, Yuting; Chamberlain Kritikos, Katie
ABSTRACT: Fitness trackers are an increasingly popular tool for tracking one's health and physical activity. While research has evaluated how these mobile devices can improve health and well-being, few studies have empirically evaluated users' privacy concerns that stem from the collection, aggregation, and sharing of personal fitness information (PFI). In this paper, we endeavor to gain a more complete picture of users' experiences with fitness trackers and how they manage the privacy of personal fitness information. Using Communication Privacy Management (CPM) as a theoretical framework, we describe findings from survey and interview data regarding the benefits and drawbacks users perceive from using a fitness tracker, as well as how privacy concerns and behaviors map onto user strategies for managing privacy boundaries related to personal fitness information. We conclude by discussing how our findings contribute to theory and future information policy related to the growing wearable device ecosystem.